PENGARUH KEBIJAKAN PENGEMBANGAN IHT (INDUSTRI HASIL TEMBAKAU) TERHADAP EKSPOR TEMBAKAU INDONESIA KE JERMAN (2009-2012) - Diajeng Andini Putri Suryanan; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This research will describes the influence of the development policy of IHT (Tobacco Industry) against Indonesian tobacco exports to Germany (2009-2012). There is a controversy of this tobacco business development. Arising from the consciousness of society and the environment make tobacco production presence was opposed by the public. Even the issue addressed by the developed countries to make a policy regarding tobacco restrictions. Framework Convention on Tobacco Control (FCTC), an international agreement of the parties (Parties) auspices of the World Health Organization (WHO) on tobacco control. Basic manufacture of this agreement is due to tobacco was considered harmful to health publik.Hal This makes the Indonesian government set a policy IHT development which is one of the priority industries in accordance with the Presidential Decree 28/2008 on National Industrial Policy. Roadmap IHT has also been arranged on Permenperin 117 / M-IND / PER / 2009. IHT development policies are structured to afford competitive in the global market by taking into account health aspects. This research shows that the development of the policy set for the export trade of tobacco have the influence. First, the German demand for imported tobacco decreased. Secondly, the selling price of tobacco also decreased and reduction in tobacco purchases because of overseas market demand reduced.Keywords : Tobacco, The development policy of IHT, Trade, Influence of Policy